1995
DOI: 10.1007/bf00990974
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic activity of proteasome on myofibrillar structures

Abstract: The physiologic function of proteasome remains unclear. Evidence suggests a role in degradation of ubiquitin-protein conjugates, MHC antigen presentation, and some specificity of substrate within certain cell types. To explore further the properties of proteasome we have examined its effect on a well defined structure, the myofibril. We find that despite its large size (20S) proteasome is able to degrade myofibrils and intact, permeabilized muscle fibrils. The proteins degraded showed some specificity because … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 16 publications
0
40
0
Order By: Relevance
“…This process is exactly reversed to the time-course of myofibril assembly, where the first organized complexes consist of α-actinin, actin and Z-disk epitopes of titin at a time when all the thick filament components are still completely diffuse throughout the sarcomere . Conversely, myofibril disassembly as it occurs during myopathies or muscle wasting is also characterized by degradation of Z-disk and I-band material before the rest of the sarcomere is affected (Taylor et al, 1995). During this process, degradation of myofibrils seems to be mainly regulated by the activity of muscle-specific calpain, which can associate with the I-band region of titin (Kinbara et al, 1998) and thereafter by the ubiquitin-proteasome pathway (Hasselgren and Fischer, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…This process is exactly reversed to the time-course of myofibril assembly, where the first organized complexes consist of α-actinin, actin and Z-disk epitopes of titin at a time when all the thick filament components are still completely diffuse throughout the sarcomere . Conversely, myofibril disassembly as it occurs during myopathies or muscle wasting is also characterized by degradation of Z-disk and I-band material before the rest of the sarcomere is affected (Taylor et al, 1995). During this process, degradation of myofibrils seems to be mainly regulated by the activity of muscle-specific calpain, which can associate with the I-band region of titin (Kinbara et al, 1998) and thereafter by the ubiquitin-proteasome pathway (Hasselgren and Fischer, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…These lysosomal and Ca 2ϩ -dependent proteinases may be qualitatively important for the degradation of specific but quantitatively minor muscle proteins. For example, calpains are involved in rapid removal of Z-disks (53,54) and N2 lines (54), and degrade nebulin, titin, troponin, tropomyosin, but not myosin and actin (53), which are quantitatively important.…”
Section: Discussionmentioning
confidence: 99%
“…Proteasomes , representing multicatalytic protease complexes , are believed to play a central role in the nonlysosomal ATPubiquitin-dependent proteolytic pathway for intracellular protein degradation (8)(9)(10)(11)(12)(13)(14). At least two forms of proteasomes are known: a 26S complex responsible for ubiquitin-conjugate degradation and requiring ATP; and a 20S proteasome (700 kD) which represents the proteolytic core of the 26S proteasome (8).…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence has indicated that the nonlysosomal ATPubiquitin-dependent proteolytic protease, as a multicatalytic protease complex (proteasome), participates in muscle wasting during various catabolic states (8)(9)(10)(11)(12)(13)(14). Degradation ofa protein via this pathway involves two distinct steps: signaling by the covalent attachment of multiple ubiquitin molecules, followed by degradation of the targeted protein by an ATP-dependent protease, the 26S (1 ,500 kD) proteasome (14), with the release of free, reutilizable ubiquitin.…”
Section: Introductionmentioning
confidence: 99%